The influence of agricultural insurance on agricultural carbon emissions: evidence from China’s crop and livestock sectors - Jin, Yue; Wang, Xinya; Wang, Qian (Frontiers in Environmental Science, 2024)
The number of tables: 11 Agricultural insurance is an important tool for promoting the development of low-carbon agriculture， which is important for achieving the goal of "Carbon Peaking and Carbon Neutrality". Using panel data from 31 provinces in China from 2001 to 2020, this study analyzes the carbon-reducing effects of agricultural insurance in both crop and livestock sectors. The results show that: (1) Agricultural insurance can decrease agricultural carbon emissions. As the stage of agricultural insurance development progresses, the carbon-reducing effects gradually increase. (2) The pathways for the carbon-reducing effects of agricultural insurance are different in the crop and livestock sectors.Agricultural insurance suppresses carbon emissions in the crop sector by adjusting the structure of crops and expanding the scale of planting, and suppresses carbon emissions in the livestock sector by expanding the scale of livestock and promoting technological progress. (3) There are regional and sectoral differences in the carbon-reducing effects of agricultural insurance. From the view of economic development, agricultural insurance is conducive to reducing carbon emissions from the crop and livestock sectors in the eastern region, but it is not significant for the central and western regions.From the view of agriculture sectors, the carbon-reducing effects of agricultural insurance on the crop sector are reflected in the agricultural area, agro-pastoral area and pastoral area; the carbon-reducing effects on the livestock sector are reflected only in agricultural area.